Knitted Strain Sensors: Impact of Design Parameters on Sensing Properties - Ozgur Atalay; William Richard Kennon (Sensors, 2014)
This paper presents a study of the sensing properties exhibited by textile-based knitted strain sensors. Knitted sensors were manufactured using flat-bed knitting technology, and electro-mechanical tests were subsequently performed on the specimens using a tensile testing machine to apply strain whilst the sensor was incorporated into a Wheatstone bridge arrangement to allow electrical monitoring. The sensing fabrics were manufactured from silver-plated nylon and elastomeric yarns. The component yarns offered similar diameters, bending characteristics and surface friction, but their production parameters differed in respect of the required yarn input tension, the number of conductive courses in the sensing structure and the elastomeric yarn extension characteristics. Experimental results showed that these manufacturing controls significantly affected the sensing properties of the knitted structures such that the gauge factor values, the working range and the linearity of the sensors varied according to the knitted structure. These results confirm that production parameters play a fundamental role in determining the physical behavior and the sensing properties of knitted sensors. It is thus possible to manipulate the sensing properties of knitted sensors and the sensor response may be engineered by varying the production parameters applied to specific designs.